Electromigration Aware Cell Design - Posser, Gracieli; Reis, Ricardo; Sapatnekar, Sachin S. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2016: Anais do XXIX Concurso de Teses e Dissertações, 2016)
Electromigration (EM) in on-chip metal interconnects is a critical reliability failure mechanism in nanometer-scale technologies. This work addresses the problem of EM on signal interconnects and on Vdd and Vss rails within a standard cell. An approach for modeling and efficient characterization of cell-internal EM is developed, incorporating Joule heating effects. We also present a graph-based algorithm that computes the currents when the pin position is moved avoiding a new characterization for each pin position and consequently reducing considerable the characterization time. We use the cell lifetime analysis to determine the lifetime of large benchmark circuits, and show that these circuit lifetimes can be improved up to 80.95% by avoiding the critical output, Vdd, and Vss pin positions of the cells, using minor layout modifications.